THE CORRELATION BETWEEN ENGLISH AS A FOREIGN LANGUAGE LEARNING READINESS AND LEARNING SATISFACTION DURING THE COVID-19 OUTBREAK - Prasetya, Wiwit; Syahid, Abdul; Sugianto, Aris (PROJECT (Professional Journal of English Education), 2021)
Online learning has been implemented as a strategic solution many universities during the Covid-19 outbreak. The aimed this research was to found correlation between students learning readiness and students satisfaction .The research employs quantitative research method using correlation design. The population of this research using random sampling was carried out 2nd-8th semester of English Education Study Program at IAIN Palangkaraya in which consist 92 respondents, in order to collected the data, the researcher was used questionnaire and analyzed with Pearson product moment correlation. The result was found that there was a positive and significant relationship between learning readiness and satisfaction with a correlation coefficient of 0.609 at the significance level α = 0.05. Learning readiness on student satisfaction is included in the strong category, which is in the range 0.61-0.80 and has a determination coefficient of 0.37, which means that the variance of satisfaction 37% is determined by the variance of learning readiness. Keywords:  Online learning, Learning Readiness, Satisfaction